Case Report: Liver and bladder metastasis in a patient with HR-positive, HER2-low breast cancer - Jiang, Lingting; Shao, Yingkuan; Chen, Qiang; Tao, Sifeng (Frontiers in Oncology, 2025)
This case report presents a premenopausal patient with high-risk hormone receptor (HR)-positive, HER2-low breast cancer who underwent breast-conserving surgery and axillary lymph node dissection after neoadjuvant chemotherapy. Despite postoperative radiotherapy, the patient did not adhere to endocrine therapy recommendations. Approximately five years later, metastases were identified in the liver, retroperitoneal lymph nodes, bones, and bladder. Notably, bladder metastasis, an exceptionally rare occurrence in breast cancer, was confirmed. Treatment with trastuzumab deruxtecan (T-DXd) demonstrated partial efficacy, though progression-free survival (PFS) was limited to six months. This case underscores the importance of vigilant follow-up and consideration of rare metastatic sites as breast cancer treatments evolve and improve. Bone-targeted therapies played a critical role, but the patient’s short PFS suggests significant tumor heterogeneity. This report discusses a rare case of bladder metastasis originating from HR-positive, HER2-low breast cancer, emphasizing innovative treatments such as T-DXd.